Evaluation of anxiety in children diagnosed with chronic urticaria - Ugur Altas; Halil Alkaya; Seda Cevik; Mehmetcan Sezer; Firat Oz; Zeynep Meva Altas; Mehmet Yasar Ozkars (Medicine Science)
This study aimed to evaluate anxiety levels in children diagnosed with chronic urticaria and to compare them with those in a healthy control group. Designed as a cross-sectional study, it included children aged 9–18 years diagnosed with chronic urticaria who attended our Pediatric Allergy and Immunology Clinic. A control group of children aged 9–18 years, free from chronic urticaria and other chronic conditions, was also included. Sociodemographic data, urticaria severity, and anxiety levels were examined. In total, data from 45 children with chronic urticaria and 43 healthy children were analyzed. Of the children with chronic urticaria, 64.4% (n=29) were female, compared to 53.5% (n=23) in the control group (p=0.296). The median ages in the chronic urticaria and control groups were 15.0 (range 7.0–18.0) and 13.0 (range 8.0–17.0), respectively (p=0.296). The state anxiety scores in children with chronic urticaria were significantly higher compared to those in the control group (p=0.010). Although trait anxiety scores were also elevated in the chronic urticaria group, the difference did not reach statistical significance (p>0.05). Additionally, while children with uncontrolled urticaria showed higher state and trait anxiety scores, these differences were not statistically significant (p>0.05). A significant positive correlation was found between age and trait anxiety (r=0.264, p=0.014). Overall, this study highlights that children with chronic urticaria tend to experience higher levels of anxiety. In clinical practice, the need for psychological support in disease management, especially in more risky groups, should be taken into consideration. [Med-Science 2024; 13(4.000): 1014-9]